2015
DOI: 10.1007/978-81-322-2517-1_9
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Molecular Single-Electron Transistors Using Silicene, Graphene and Germanene

Abstract: By using Ab initio approach, we have analysed Silicene-, Germaneneand Graphene-based molecular single-electron transistors. It is based on non-equilibrium greens function (NGEF) and density functional theory (DFT). Three different fullerene molecules are taken and optimization is done. In Coulomb blockade regime, silicene, germanene and graphene are kept above gate dielectric between drain and source for weak coupling. We have taken gold electrodes for SET environment. Gold is widely used as metal electrode in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 23 publications
0
4
0
Order By: Relevance
“…105 In the figure, the two dotted lines are perpendicular to each other, indicating that the angle between the (0002) and (11)(12)(13)(14)(15)(16)(17)(18)(19)(20) planes was 90 . In addition, the interlayer spacing of the multilayered germanene, directly estimated from the TEM image, was $0.197 nm, which implies that these layers were parallel to the (11)(12)(13)(14)(15)(16)(17)(18)(19)(20) plane.…”
Section: Plasma-assisted Synthesismentioning
confidence: 97%
See 3 more Smart Citations
“…105 In the figure, the two dotted lines are perpendicular to each other, indicating that the angle between the (0002) and (11)(12)(13)(14)(15)(16)(17)(18)(19)(20) planes was 90 . In addition, the interlayer spacing of the multilayered germanene, directly estimated from the TEM image, was $0.197 nm, which implies that these layers were parallel to the (11)(12)(13)(14)(15)(16)(17)(18)(19)(20) plane.…”
Section: Plasma-assisted Synthesismentioning
confidence: 97%
“…A high-magnification transmission electron microscopy (TEM) image of the final product (Figure 5C) showed that the synthesized multilayered germanene was approximately 2 nm thick with approximately 6-7 layers. The fast Fourier transform analysis of the diffraction pattern shown in Figure 5C inset reveals that the reciprocal lattice points along the blue dashed line indicate the lattice planes parallel to the (0002) plane, while those along the green dashed line represent the lattice planes parallel to the (11)(12)(13)(14)(15)(16)(17)(18)(19)(20) plane. The interplanar spacing of (0002) and (11)(12)(13)(14)(15)(16)(17)(18)(19)(20) were equal to $0.306 and $0.198 nm, respectively, which are consistent with the first principles results.…”
Section: Plasma-assisted Synthesismentioning
confidence: 99%
See 2 more Smart Citations